Acetabular remodeling after closed reduction of developmental dysplasia of the hip - Hayazi M Al Shehri; Asim A Mahmoud; Saleh A Ateeq; Amal H Alamrani (Saudi Journal of Medicine and Medical Sciences, 2018)
Objectives: This study aims to assess the radiographic development of the acetabulum after closed reduction of developmental dysplasia of the hip in patients with different follow-up periods. Methods: The authors undertook a retrospective review of clinical records and radiographs of children who were diagnosed with developmental dysplasia of the hip and underwent closed reduction (mean age at closed reduction: 8.6 months) at King Khalid Civil Hospital, Tabuk, Saudi Arabia. Patients with a follow-up period < 12 months were excluded from the study. Acetabular index angles for anteroposterior pelvic radiograph before treatment and at the final follow-up were used to assess acetabular development. Patients were divided into four groups according to the follow-up period and then the acetabular index was compared. Results: A total of 64 dislocated hips of 40 patients were included in the study. The average follow-up period was 33.9 months (range: 12–82 months). Mean acetabular index before closed reduction was 34.37° (range: 25–46°), whereas the mean acetabular index after closed reduction was 23.8° (range: 10–37°). All groups showed improvement in the acetabular coverage and the acetabular index was significantly higher in groups with a longer follow-up period. Conclusions: This study found that successful closed reduction of congenitally dislocated hips within the recommended age results in better acetabular development (coverage) and this improvement is more evident in patients with a longer follow-up period. Further studies can consolidate these results and help define the criteria for deciding early acetabuloplasty.